Enantiomeric determination of tramadol and O-desmethyltramadol in human plasma by fast liquid chromatographic technique coupled with mass spectrometric detection - Chytil, Lukáš; Matoušková, Olga; Černá, Olga; Pokorná, Pavla; Vobruba, Václav; Perlík, František; Slanař, Ondřej (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2010)
A rapid and sensitive method using liquid chromatography-tandem mass spectrometry (LC-MS/MS) for enantiomeric determination of tramadol and its primary phase metabolite O-desmethyltramadol in human plasma has been developed. Tramadol hydrochloride-(13)C, d(3), was used as an isotopic labeled internal standard for quantification. The method involves a simple solid phase extraction. The analytes and internal standard were separated on Lux Cellulose-2 packed with cellulose tris(3-chloro-4-methylphenylcarbamate) using isocratic elution with hexane/isopropanol/diethylamine (90:10:0.1, v/v/v) at a flow rate of 1.3 mL/min. The APCI positive ionization mass spectrometry was used with multiple reaction monitoring of the transitions at m/z 264.2-->58.2 for tramadol, m/z 250.1-->58.2 for O-desmethyltramadol and m/z 268.2-->58.2 for internal standard. Linearity was achieved between 1-800 ng/mL and 1-400 ng/mL (R(2) > or = 0.999) for each enantiomer of tramadol and O-desmethyltramadol, respectively. Intra-day accuracies ranged among 98.2-102.8%, 97.1-109.1% and 97.4-102.9% at the lower, intermediate, and high concentration for all analytes, respectively. Inter-day accuracies ranged among 95.5-104.1%, 99.2-104.7%, and 94.2-105.6% at the lower, intermediate, and high concentration for all analytes, respectively. This assay was successfully used to determine the concentration of enantiomers of tramadol and O-desmethyltramadol in a pharmacogenetic study.
Keywords: Limit of Detection; stereoizomerie; limita detekce; Chromatography, Liquid; Humans; extrakce na pevné fázi; Tramadol; tramadol; Phenotype; lidé; Stereoisomerism; reprodukovatelnost výsledků; časové faktory; chromatografie kapalinová; cytochrom P-450 CYP2D6; Reproducibility of Results; Cytochrome P-450 CYP2D6; fenotyp; Solid Phase Extraction; hmotnostní spektrometrie; Time Factors; kalibrace; Calibration; Mass Spectrometry